Eduwisata Pengelolaan TPS Sumur Wolu Desa Sambit Menuju Desa Berdaya - Ridho, Irvan Nur; Triono, Bambang; Pinaryo, Pinaryo (Gulawentah:Jurnal Studi Sosial, 2024)
Educational tourism is a type of tourism where visitors have the goal of learning about a specific topic. Therefore, the development of educational tourism is not supported by good human resources in its management, so it is very unlikely that the development of educational tourism can run well. Garbage waste has an impact on every element of life, including health, pollution, environmental damage, and natural disasters. In line with the Ministry of Tourism and Creative Economy, development efforts to support the development of existing tourism potential, the community is involved in the development process. The research method used is qualitative research with a descriptive approach. The 3R waste management method provides the community with new perspectives and insights into waste management. The 3R approach can turn waste into something that has added value rather than just a useless commodity. Independent waste management educational tourism is an alternative solution for the government and the community. To carry out the management of the waste bank in Sambit